Making EU economic governance fit for purpose: Investing in the future and reforming the fiscal rules while decentralizing and democratizing - Vivien A. Schmidt (EconPol Forum, 2023)
The EU needs a permanent EU debt facility to address its many existential challenges, including climate change, energy, inequality, and security related to the Ukraine crisis. The EU's fiscal rules need to be fit for purpose, meaning that rather than primarily targeting debt-reduction they need to be focused on investment to meet the EU's many challenges. Germany is the elephant in the room when it comes to obstacles to fit-for-purpose fiscal rules and EU level investment capacity, The European Semester should be decentralized and democratized at the national level to ensure effective national "ownership" and legitimacy. The EU's economic governance should also be democratized through strategic dialogues focused on macroeconomic policy and industrial policy, The dangers of populist extremism can be addressed only by developing common solutions that recognize the interdependence of the EU's economies and the need to address the EU's many existential challenges through EU solidarity, including EU leveldebt and fit-for-purpose fiscal rules
Keywords: 330